Betanodavirus ability to infect juvenile European sea bass, Dicentrarchus labrax , at different water salinity - F Pascoli; M Serra; M Toson; T Pretto; A Toffan (Journal of Fish Diseases, 2016)
Viral encephalopathy and retinopathy ( VER ) is one of the most devastating and economically relevant diseases for marine aquaculture. The presence of betanodavirus in freshwater fish is recorded, but very little is known about VER outbreaks in marine species reared in freshwater. Our study investigated the ability of betanodavirus to cause disease in European sea bass, Dicentrarchus labrax, reared at different salinity levels. Fish were challenged with RGNNV or mock infected by bath at different salinity levels (freshwater, 25‰ and 33‰). Fish were checked twice a day and the dead ones were examined by standard virological techniques, by rRT ‐ PCR and by histochemical and immunohistochemical analyses. All the infected groups showed a significant higher mortality rate than the one of the mock‐infected group. VER v presence was confirmed by rRT ‐ PCR . Histochemical and immunohistochemical analyses highlighted the typical lesions associated with VER . Our results highlight that salinity does not affect the ability of betanodavirus to induce clinical signs and mortality in European sea bass infected under experimental conditions. These results underline the great adaptation potential of VER v, which in combination with its already known high environmental resistance and broad host range, may explain the diffusion of this disease and the threat posed to aquaculture worldwide.